Distribution of the CCR5-delta32 deletion in Southwest Germany - Hütter, Gero; Blüthgen, Christian; Elvers-Hornung, Susanne; Klüter, Harald; Bugert, Peter (Journal of biological and clinical anthropology, 2015)
A 32 base pair deletion in the c-c chemokine receptor gene 5 (CCR5) leads to an inactive protein. Carriers of this deletion must have had a selective advantage because the allelic frequency of the CCR5-delat32 mutation is much higher than expected. Furthermore, there is a decline from North to South Europe. For Germany there are just very few cross-sectional surveys available. Here we investigated a large number of healthy blood donors from Northern Baden-Wuerttemberg. We observed an allelic frequency of 9.21 % of the CCR5-delta32 deletion. The distribution did not follow the Hardy-Weinberg equilibrium suggesting that homozygous carriers of the deletion were overrepresented in this random sample.
Gesehen am 23.05.2017